2013
DOI: 10.1016/j.neuroimage.2013.05.089
|View full text |Cite
|
Sign up to set email alerts
|

Digital reconstruction and morphometric analysis of human brain arterial vasculature from magnetic resonance angiography

Abstract: Characterization of the complex branching architecture of cerebral arteries across a representative sample of the human population is important for diagnosing, analyzing, and predicting pathological states. Brain arterial vasculature can be visualized by magnetic resonance angiography (MRA). However, most MRA studies are limited to qualitative assessments, partial morphometric analyses, individual (or small numbers of) subjects, proprietary datasets, or combinations of the above limitations. Neuroinformatics t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 79 publications
(88 reference statements)
7
102
2
1
Order By: Relevance
“…Hotz et al (2013), followed by Barden, Le and Owen (2013, 2014), investigated surprising nonstandard central limit theory in phylogenetic tree spaces. Finally, an analysis [Wright et al (2013)] of a different, and smaller, set of MRA brain artery images also found a connection between vessel length and healthy aging.…”
Section: Brain Artery Treesmentioning
confidence: 98%
“…Hotz et al (2013), followed by Barden, Le and Owen (2013, 2014), investigated surprising nonstandard central limit theory in phylogenetic tree spaces. Finally, an analysis [Wright et al (2013)] of a different, and smaller, set of MRA brain artery images also found a connection between vessel length and healthy aging.…”
Section: Brain Artery Treesmentioning
confidence: 98%
“…Centerlines are widely accepted representations of arterial networks [31,36,37,[45][46][47][48], because they retain most of the geometric characteristics of arteries in a more compact and simpler structure. Three-dimensional centerlines are represented by polylines with point-wise information (e.g., lumen radius).…”
Section: Centerline Modelmentioning
confidence: 99%
“…Such work also made use of the large deformation diffeomorphic metric curve mapping [52] to provide correspondences between centerlines and to define a metric in shape space. Wright et al [36] performed statistical analysis of morphometric variables (e.g., size, distances, angles, and branching structure) of the brain arterial vasculature; it was extended and complemented by Mut et al [37] by describing the sample-averaged shape and geographic distribution of the brain arterial trees based on a probabilistic vascular atlas.…”
Section: Arterial Characterization and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Também usamos duas imagens de angiografia reais, nas quais os centros de linha e os diâmetros foram obtidos por procedimentos manuais. Concernente aos testes de correspondência entre redes vasculares, usamos um dataset de 57 imagens, baseadas no projeto Brava [Wright et al, 2013].…”
Section: Conjunto De Imagensunclassified